Onlay block bone grafting in alveolar distraction osteogenesis to increase callus volume - DERGİN, GÜHAN (My University, 2010)
The functional and esthetical rehabilitation of the maxilla with dental implants when there is a severe alveolar bone deficiency can be achieved with the help of distraction osteogenesis. Although this method offers certain advantages over conventional augmentation methods, it sometimes requires secondary bone grafting because the bone of the transport segment may be too thin and semilunar excavations may form in the distraction zone. In this situation, the simultaneous application of distraction osteogenesis with a polytetrafluoroethylene membrane and autogenous onlay block bone grafting is an alternative solution to secondary bone grafting. In addition, this technique prevents semilunar excavations in the distraction zone and increases callus volume.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry